2011
DOI: 10.2176/nmc.51.187
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Subarachnoid Hemorrhage by Three-Dimensional Computed Tomography: Correlation Between Hematoma Volume and Symptomatic Vasospasm

Abstract: Subarachnoid hemorrhage (SAH) volume was measured by three-dimensional computed tomography (3D-CT) and the correlation examined between the SAH volume and the occurrence of symptomatic vasospasm (SVS). Experimental (in vitro) hematomas were made with blood obtained from 10 volunteers. The hematoma volume was determined by actual measurements and by 3D-CT using a CT number in the range of 40-80 Hounsfield units (HU) on days 1, 4, 7, 11, and 14. The coefficients on days 1 and 4 were relatively high and the corre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Sato et al 23 proposed an automated measurement on 3D CT to quantify SAH on the basis of thresholding between 40 and 80 HU, which could rapidly measure SAH volume. However, the time needed to manually exclude the scalp and subcutaneous tissue was not taken into account.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sato et al 23 proposed an automated measurement on 3D CT to quantify SAH on the basis of thresholding between 40 and 80 HU, which could rapidly measure SAH volume. However, the time needed to manually exclude the scalp and subcutaneous tissue was not taken into account.…”
Section: Discussionmentioning
confidence: 99%
“…A quantitative volume and density measurement may reduce interobserver variability in comparison with current scales and would provide physicians with a potentially valuable tool for outcome prediction and treatment guidance. 23 As such, the aim of this study was to design and validate a reliable and easy-to-apply automatic measurement for subarachnoid hemorrhage quantification.…”
mentioning
confidence: 99%
“…More recently, Ko et al 14 used personal computer-based software to quantify volumes in DICOM images, and showed that the quantitation of SAH is feasible, and that both cisternal and total bleeding volume are related to both the development of DCI and outcome. Sato et al 29 developed a method to quantify SAH on 3D CT, which yields volume data in less time than with 2D techniques. In this method, hemorrhage volume within the different compartments is determined based on blood Hounsfield units.…”
Section: Discussionmentioning
confidence: 99%